Strength training and anabolic steroids: a comparative study of the vastus lateralis, a thigh muscle and the trapezius, a shoulder muscle, of strength-trained athletes - Eriksson, A. (2006)
Strength training is widely used to increase performance in sports with high physical demands. The use of drugs such as anabolic steroids among athletes is a wellknown phenomenon, and the effects of these drugs on physical performance documented. The studies presented in this thesis focused on the mechanisms of muscle fiber hypertrophy in the vastus lateralis and the trapezius muscles of strength trained elite athletes. The main hypothesis was that the muscle adaptations to strength training and anabolic steroids are muscle specific. Biopsies were obtained from the trapezius and the vastus lateralis from three groups of elite power lifters. Nine used drugs, ten did not and seven had previously used drugs. Six sedentary males served as controls. The biopsies were frozen and cut in serial cross sections. Histological and immunohistochemical staining techniques were used to analyze muscle fiber morphology and pathology. Fiber type distribution, fiber area, myonuclei number and distribution, satellite cell number and proportion of split fibers were counted and compared for the two muscles within and between the groups. The main findings were that: a) Muscle fiber hypertrophy by strength training is further increased by anabolic steroids. b) The number of nuclei per muscle fiber is higher in power lifters using anabolic steroids compared to non-steroids using lifters. c) Among power lifters who have withdrawn from anabolic steroid usage and training for several years, the number of myonuclei, both subsarcolemmal and internal, remains high. d) In active power lifters, anabolic steroids have no further effect on the number of satellite cells per fiber. e) Power lifters have a high proportion of split fibers. High intensity resistance training increases muscle strength and banned substances such as testosterone and anabolic steroids can enhance the training effects. The studies on muscle cell morphology presented in this thesis reveals that anabolic steroids and testosterone increases muscle fiber size and adds more nuclei to the muscle cell. Based on the morphological appearance of muscle sections from doped and nondoped power lifters, we conclude that testosterone and anabolic steroids enhances the hypertrophic effects of training without adding new features. The addition of myonuclei by training and doping appears t o be longer lasting in some muscles than in others. The high proportion of split fibers in power lifter is probably due to high mechanical stress. The findings and conclusions in this thesis raise questions regarding relevant suspension times for athletes caught with banned substances in the body.